1999
DOI: 10.1016/s0014-5793(99)01680-4
|View full text |Cite
|
Sign up to set email alerts
|

Binding of IL‐4 to the IL‐13Rα1/IL‐4Rα receptor complex leads to STAT3 phosphorylation but not to its nuclear translocation

Abstract: Interleukin-4 (IL-4) is a pleiotropic cytokine, which acts on both hematopoietic and non-hematopoietic cells, through different types of receptor complexes. In this study, we report that in human B cells, IL-4 caused rapid phosphorylation of Janus kinase (JAK) 1 and JAK3 tyrosine kinases. In keratinocytes, the hematopoietic-specific receptor common Q Q c chain is not expressed and the IL-13 receptor K K 1 (IL-13RK K 1 ) participates in IL-4 signal transduction. In keratinocytes, IL-4 induced JAK1 and JAK2 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…The results presented here are consistent with our previous ®ndings which have indicated that in keratinocytes, in contrast to hematopoietic cell lines, IL-4 also induced ERK activation (Wery et al, 1996). In A431 cells, we and others have demonstrated that the nature of the IL-4R is dierent from hematopoietic cell lines (Murata et al, 1997;Wery-Zennaro et al, 1999). The characterization of IL-4R, reported in a larger number of cell lines, indicated that only hematopoietic cells signi®cantly expressed g c .…”
Section: Discussionsupporting
confidence: 92%
“…The results presented here are consistent with our previous ®ndings which have indicated that in keratinocytes, in contrast to hematopoietic cell lines, IL-4 also induced ERK activation (Wery et al, 1996). In A431 cells, we and others have demonstrated that the nature of the IL-4R is dierent from hematopoietic cell lines (Murata et al, 1997;Wery-Zennaro et al, 1999). The characterization of IL-4R, reported in a larger number of cell lines, indicated that only hematopoietic cells signi®cantly expressed g c .…”
Section: Discussionsupporting
confidence: 92%
“…precipitation assay was carried out as described previously (34). In brief, the following 59 biotin-labeled single-stranded oligonucleotides were hybridized: 59-ACT GCG AAC ATT TCG CTT TCATTT TGG-39 and 59-CCA AAATGA AAG CGA AAT GTT CGC AGT-39 (MWG Biotech, Ebersberg, Germany) according to the human IFN sequence response element (ISRE) consensus sequence from the IL-12p35 promoter.…”
Section: Chemical Treatment Of Idcsmentioning
confidence: 99%
“…The Jak-STAT pathway has been shown to be activated by IL-4. Activation of JAK1 and JAK2 or 3, depending on the cell lines, is pivotal for the activation of downstream signaling events including the recruitment and rapid tyrosine phosphorylation of STAT6 (1)(2)(3)(4). STAT6 can dimerize and translocate into the nucleus where it regulates IL-4 target genes.…”
Section: Interleukin (Il)mentioning
confidence: 99%